APLIKASI KIMIA KOMPUTASI DALAM HUBUNGAN STRUKTUR AKTIVITAS SENYAWA ANALOG TURUNAN QUINOLIN DARI Cinchona ledgeriana Moens SEBAGAI ANTIMALARIA - Nur Syamsi Dhuha; Muhammad Aswad; Haeria Haeria (Universitas Islam Negeri Alauddin Makassar, 2014)
Study of QSAR explains quantitative relation between molecular structure and biological activity of molecule. QSAR analysis to the 16 analogues of quinoline compound as antimalarial agents had been done by using physicochemical properties like netto atom charge, total energy, binding energy, electronic energi, heat of formation, moment dipol, volume, hydration energi, log P, refractivity, polarisability, mass, HOMO energy, and LUMO energy as predictors. Calculation of the physicochemical properties was conducted with semiempirik AMI method, while the compound activity obtained from literature. Statistical analysis and the best valid equation based on statistical criteria of analytical regression and leave-one-out cross validation. The result showed that physicochemical properties of Quinoline Analogues which correlate to antimalarial activities are partial charge in several atoms and LUMO energy.